A Qualitative Inquiry on Instructional Strategies and Assessments in Teaching Social Science General Education Courses in the Online Learning Modality - Mayo-Dosayla, Charity Mae; Madrigal, Dennis; Dioso, Dexter Paul (Technium Social Sciences Journal, 2022)
The immediate transitioning of instructional delivery from the traditional face-to-face teaching to online learning prompted college instructors to design pedagogical strategies and assessment tools appropriate for the online learning environment. Instructional strategies and assessments in teaching Social Science general education courses online in the context of state universities and colleges (SUCs) however have not been previously established. Anchoring on social constructivism, post-positivism, and pragmatism, this qualitative inquiry was conducted to determine the teaching methods and assessments employed by social science instructors in SUCs in teaching Readings in Philippine History and Life and Works of Rizal online. Semi-structured interviews were conducted with 7 social science instructors from 6 SUCs. Member checking and audit trail by a qualitative research expert were used for data trustworthiness and Lichtman’s 3 Cs was used for data analysis. The qualitative inquiry revealed 7 major themes for online instructional strategies: blended learning activities; synchronous online activities; interactive lecture discussion; group reporting; short videos and films presentation; use of modules in print and soft copy; and advanced readings. Likewise, 5 themes for online assessment were identified: objective test; subjective test; term examination; group projects; and output-making. Results of the study revealed that the instructional strategies and assessments used are constructively aligned with the learning outcomes set in the CHED-prescribed course syllabus but are still the traditional types. Instructors therefore only migrated their teaching practice from the in-person classroom instruction to the online mode.